2021
DOI: 10.3390/su132413541
|View full text |Cite
|
Sign up to set email alerts
|

Facilitating Servitization in Manufacturing Firms: The Influence of Strategic Orientation

Abstract: Servitization has significant implications for the sustainable development of manufacturing, the economy, and the environment. However, it does not always produce returns as the firms expect, which may discourage them from engaging in this transition. In this study, we examine the facilitating effects of two dimensions of strategic orientation (i.e., technology and market orientation) on two types of servitization (i.e., basic and advanced service provision), and further investigate the performance impacts of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 85 publications
(233 reference statements)
0
13
0
Order By: Relevance
“…Specifically, building dynamic capabilities can, first of all, help enterprises improve their sensitivity and adaptability to the external environment (Akter et al, 2021), grasp opportunities and identify risks. Secondly, adjust and optimize internal and external resources to form unique competitive advantages (Zhang et al, 2021). Thirdly, combine new knowledge with internal knowledge to promote service innovation and the long-term sustainable development of the firm (Razmdoost et al, 2020).…”
Section: Dynamic Capability Theorymentioning
confidence: 99%
See 2 more Smart Citations
“…Specifically, building dynamic capabilities can, first of all, help enterprises improve their sensitivity and adaptability to the external environment (Akter et al, 2021), grasp opportunities and identify risks. Secondly, adjust and optimize internal and external resources to form unique competitive advantages (Zhang et al, 2021). Thirdly, combine new knowledge with internal knowledge to promote service innovation and the long-term sustainable development of the firm (Razmdoost et al, 2020).…”
Section: Dynamic Capability Theorymentioning
confidence: 99%
“…, 2021), grasp opportunities and identify risks. Secondly, adjust and optimize internal and external resources to form unique competitive advantages (Zhang et al. , 2021).…”
Section: Literature Review and Theoretical Foundationmentioning
confidence: 99%
See 1 more Smart Citation
“…Kohtamäki et al (2020) provided the concept that servitization in manufacturing is a process of transition from standardized products and additional services to customized and advanced services. Previous research on business-to-business (B2B) servitization mainly revealed the servitization framework from a comprehensive perspective (Baines et al , 2017; Raddats et al , 2019; Zhang et al , 2021). It is a continuous transformation for manufacturers, who increasingly integrate services into their business landscape (Forkmann et al , 2017; Niu et al , 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the study frames the research issue of servitization innovation from a B2B perspective. In addition, exploring the mechanism behind actor engagement will help to examine the antecedents for B2B servitization in the business ecosystem (Zhang et al , 2021). That is, by examining possible antecedents and mechanisms, it helps to consolidate the understanding of B2B servitization.…”
Section: Introductionmentioning
confidence: 99%